2007
DOI: 10.1029/2006gl028588
|View full text |Cite
|
Sign up to set email alerts
|

Relation between sea level and bottom pressure and the vertical dependence of oceanic variability

Abstract: [1] The relation between large-scale sea level and bottom pressure variability is studied using long (50-yr) simulations of a general circulation model under realistic forcing. Admittance and coherence analyses are used to characterize the bottom pressure and sea level relationship as a function of period, horizontal spatial scale, and location. At the model grid scale (1°), bottom pressure is found to be essentially equivalent to sea level at periods <30 days, except in the tropics. This equivalence still hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
100
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 18 publications
20
100
2
Order By: Relevance
“…Send, Scripps Institution of Oceanography, La Jolla, United States, Figure 13) likewise reported by Bryden et al [2009] from the oceanographic RAPID array more than 1000 km further north in the Atlantic Ocean at 26°N. Also our results support the conclusion from the modeling of Vinogradova et al [2007] who found the sea level and bottom pressure to be increasingly uncorrelated toward lower latitudes.…”
Section: Satellite Altimetrysupporting
confidence: 82%
“…Send, Scripps Institution of Oceanography, La Jolla, United States, Figure 13) likewise reported by Bryden et al [2009] from the oceanographic RAPID array more than 1000 km further north in the Atlantic Ocean at 26°N. Also our results support the conclusion from the modeling of Vinogradova et al [2007] who found the sea level and bottom pressure to be increasingly uncorrelated toward lower latitudes.…”
Section: Satellite Altimetrysupporting
confidence: 82%
“…This work is in a sense an observational perspective of the work of Vinogradova et al (2007) and Bingham and Hughes (2008). Based on the results from this paper, at the time scales and the places where the Arctic Ocean is barotropic (i.e., predominantly on the shelves), GRACE OBP may be used to identify SSH variations.…”
Section: Discussionmentioning
confidence: 94%
“…The dominance of the barotropic contribution over the baroclinic contribution to OBP variations depends on depth, latitude, time scale, and stratification (Gill and Niiler 1973;Vinogradova et al 2007;Bingham and Hughes 2008). Modeling studies indicate that at high latitudes (Vinogradova et al 2007) and at the Arctic Ocean in particular , and at annual and shorter time scales, the circulation is predominantly barotropic, whereas at interannual and longer time scales, circulation adjusts baroclinically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Values are of the order of 0.8 or higher in the tropical regions and decrease to 0.6 north of 40 • N and to 0.3-0.4 south of 40 • S. The low values of the regression coefficients at high latitudes are due to strong barotropic signal and deep baroclinic signals (Vinogradova et al, 2007). This leads to an underestimation of the steric part of the sea level by DHA calculated using a 1000 m depth reference level (Fig.…”
Section: Correlation Between Argo and Altimeter Observationsmentioning
confidence: 94%